Pengawasan Orang Tua Dalam Penggunaan Gadget Pada Anak Usia Dini Selama Masa Pandemi COVID-19 - Cau Kim Jiu; Kharisma Pratama; Jaka Pradika; Hartono Hartono; Indri Erwhani (UIN Sultan Maulana Hasanuddin Banten, 2022)
Changes in the learning process during the pandemic from classroom learning to online learning certainly cannot be separated from the role of gadgets, but for early childhood the online learning process using gadgets needs to get supervision from parents to minimize negative impacts. This study aims to explore the way parents monitor the use of gadgets during the Covid-19 pandemic in early childhood aged 4-6 years at Aisyiyah Kindergarten Bustanul Athfal 6 Pontianak City. This research is a qualitative research. Data were obtained through in-depth interviews and Focus Group Discussions. Participants in this study consisted of 10 mothers who had early childhood. There are 4 themes found in this study, namely 1) managing the time of using gadgets, 2) limiting access, 3) giving passwords to gadgets and 4) giving rewards and punishments. This study concludes that to reduce the negative impact and addiction to gadgets, parental supervision is needed in the use of gadgets. Keywords: parental supervision; gadgets; the Covid-19 pandemic; early childhood References Agung, I., Widiputera, F., & Widodo, W. (2019). The Effect of The use of Gadget on Psychosocial, Socio- Emotional, Self-Reliance, Responsibility, and Students Learning Results in Elementary School. Education Quarterly Reviews, 2(2), 276–291. https://doi.org/10.31014/aior.1993.02.02.60 Alifia, U., Barasa, A. R., Bima, L., Pramana, R. P., Revina, S., & Tresnatri, F. A. (2020). Learning from Home: Portrait of Teaching and Learning Inequalities in Times of The Covid-19 Pandemic. Smeru Research Institute, 1(1), 1–8. Amaliah, S., Maryani, K., & Khosiah, S. (2022). Hubungan Menonton Video Youtube Dengan Kemampuan Komunikasi Anak Usia 5 -6 Tahun. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 7(1), 121–132. Azizah, N., & Dewi, A. C. (2021). Analisis Perkembangan Bahasa Semantik Dan Sintaksis Anak Dalam Kegiatan Belajar Dari Rumah. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 139–146. Braun, V., & Clarke, V. (2006). Using thematic analysis in psychology Using thematic analysis in psychology. Qualitative Research in Psychology, 3(2), 77–101. https://doi.org/http://dx.doi.org/10.1191/1478088706qp063oa Dong, C., Cao, S., & Li, H. (2020). Young children ’ s online learning during COVID-19 pandemic : Chinese parents ’ beliefs and attitudes. Children and Youth Services Review, 118, 1–9. https://doi.org/https://doi.org/10.1016/j.childyouth.2020.105440 Febianti, Y. N. (2018). Peningkatan Motivasi Belajar dengan Reward and Punishment yang Positif. Jurnal Edunomic, 6(2), 93–102. Garbe, A., ogurlu, U., Logan, N., & Cook, P. (2020). Parents’ Experiences with Remote Education during COVID-19 School Closures. American Journal of Qualitative Research, 4(3), 45–65. https://doi.org/10.29333/ajqr/8471 Imroatun, I., Widat, F., Fauziddin, M., Farida, S., Maryam, S., & Zulaiha. (2021). Youtube as a Media for Strengthining Character Education in Early Childhood. Journal of Physics: Conference Series, 1779(1), 012064. https://doi.org/10.1088/1742-6596/1779/1/012064 Maqsudah, N., & Setyowati, rina isnani. (2020). Pemanfaatan Youtube Sebagai Media Belajar Anak Usia Dini di Masa Covid-19 Berbasis Merdeka Belajar. Prosiding Webinar Jurusan KSDP FIP-UM, 95–101. Mulyati, M. (2019). Menciptakan Pembelajaran Menyenangkan Dalam Menumbuhkan Peminatan Anak Usia Dini Terhadap Pelajaran. Alim Journal of Islamic Education, I(2), 277–294. Neumann, M. M., Merchant, G., & Burnett, C. (2018). Young children and tablets: the views of parents and teachers. Early Child Development and Care, 1–12. https://doi.org/10.1080/03004430.2018.1550083 Putri, R. S., Purwanto, A., Pramono, R., Asbari, M., Wijayanti, L. M., & Hyun, C. C. (2020). Impact of the COVID-19 pandemic on online home learning: An explorative study of primary schools in Indonesia. International Journal of Advanced Science and Technology, 29(5), 4809–4818. Quthosi, S. B., Deeba, F., & Khan, S. (2020). The Impact of Technological Gadgets on the Socialization of Children at Early Childhood Developmental Stage. Journal of Development and Social Sciences, 1(3), 55–66. https://doi.org/10.47205/jdss.2020(1-iii)6 Qutoshi, S. B., Ali, S., & Khan, S. (2021). Use of Technological Gadget and its Effects on Children at Agah Walidain Program and Beyond during Covid-19 Pandemic Lockdown. International Review of Social Sciences, 9(2), 22–32. Rachmaniar, R., Prihandini, P., & Janitra, P. A. (2018). Perilaku Penggunaan Smartphone dan Akses Pornografi di Kalangan Remaja Perempuan. Jurnal Komunikasi Global, 7(1), 1–11. https://doi.org/10.24815/jkg.v7i1.10890 Rahiem, M. D. H., & Novi, A. (2022). Home Visit Sebagai Metode Pembelajaran Anak Usia Dini Pada Masa COVID-19. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 7(1), 83–102. Rosiyanti, H., & Muthmainnah, R. N. (2018). Penggunaan Gadget Sebagai Sumber Belajar Mempengaruhi Hasil Belajar Pada Mata Kuliah Matematika Dasar. FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 4(1), 25–36. https://doi.org/10.24853/fbc.4.1.25-36 Sandelowski, M. (2000). Whatever Happened to Qualitative Description? Res Nurs Health, 23(4), 334–340. https://doi.org/doi: 10.1002/1098-240x(200008)23:43.0.co;2-g Sari & Maningtyas. (2020). Parents’ Involvement in Distance Learning During the Covid-19 Pandemic. Advances in Social Science, Education and Humanities Research. Proceedings of the 2nd Early Childhood and Primary Childhood Education (ECPE 2020), 487, 94–97. Serra, G., Lo Scalzo, L., Giuffrè, M., Ferrara, P., & Corsello, G. (2021). Smartphone use and addiction during the coronavirus disease 2019 (COVID-19) pandemic: cohort study on 184 Italian children and adolescents. Italian Journal of Pediatrics, 47(150), 1–10. https://doi.org/10.1186/s13052-021-01102-8 Setiani, D. (2020). The Effect of Gadget Usage on the Social Development of Children Aged 3-5 Years: Literature Review. STRADA Jurnal Ilmiah Kesehatan, 9(2), 1732–1739. https://doi.org/10.30994/sjik.v9i2.526 Siahaan, C. (2021). The Challenge of Parents as Guide in Online Learning of Elementary School. Proceedings of the 2nd Annual Conference on blended learning, educational technology and Innovation (ACBLETI 2020), 560, 78–83. Srinahyanti, S., Wau, Y., Manurung, I., & Arjani, N. (2019). Influence of Gadget: A Positive and Negative Impact of Smartphone Usage for Early Child. ACEIVE. https://doi.org/10.4108/eai.3-11-2018.2285692 Sundus, M. (2018). The Impact of using Gadgets on Children. Journal of Depression and Anxiety, 07(01), 1–3. https://doi.org/10.4172/2167-1044.1000296 Susilowati, I. H., Nugraha, S., Alimoeso, S., & Hasiholan, B. P. (2021). Screen Time for Preschool Children: Learning from Home during the COVID-19 Pandemic. Global Pediatric Health, 8. https://doi.org/10.1177/2333794X211017836 Wahyuni, A. S., Siahaan, F. B., Arfa, M., Alona, I., & Nerdy, N. (2019). The relationship between the duration of playing gadget and mental emotional state of elementary school students. Open Access Macedonian Journal of Medical Sciences, 7(1), 148–151. https://doi.org/10.3889/oamjms.2019.037